'We do need to keep some human touch'—Patient and clinician experiences of ovarian cancer follow‐up and the potential for an electronic patient‐reported outcome pathway: A qualitative interview study. (10th February 2022) - Kennedy, Fiona; Shearsmith, Leanne; Holmes, Marie; Peacock, Rosemary; Lindner, Oana C.; Megson, Molly; Velikova, Galina
Abstract: Objective: This study aimed to explore experiences of follow‐up after treatment and views on an electronic patient‐reported outcome (ePRO) pathway among ovarian cancer patients and clinicians. Methods: Semi‐structured qualitative interviews were conducted with clinicians and patients previously treated for ovarian cancer. Interviews explored experiences of the current follow‐up pathway, patients' needs and views on an ePRO pathway enabling patients to report symptoms online rather than attend clinic‐based appointments. Transcripts were analysed using framework analysis. Results: Sixteen patients and 10 clinicians participated from four hospitals in England. Four key themes were identified: transition into follow‐up, key features of effective follow‐up, issues in follow‐up and views of ePRO. Both patients and clinicians saw benefits of an ePRO pathway alongside continued access to specialist support and discussed various practicalities (e.g., frequency, introduction and communication). Technology concerns and feelings of abandonment were highlighted as barriers. The proposed impact on clinical and individual patient outcomes was discussed. Conclusion: Patient and clinician views on follow‐up and an ePRO pathway informed key recommendations on the development/introduction of ePRO follow‐up. Technology use in healthcare will continue to grow and may offer solutions to facilitate responsive and tailored care. Further research should explore the safety, experiences and acceptability of ePRO follow‐up.